Implementation of the Marriage Management Information System (SIMKAH) in the Religious Affairs Office, Central City District, Gorontalo City - Gintulangi, Sabriana Oktaviana; Habsy, Alan dwiyan (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to analyze the implementation of the Marriage Management Information System (SIMKAH) in the Religious Affairs Office (KUA) in Tengah City, Gorontalo City. Through a descriptive qualitative approach, researchers explored and analyzed information related to the effectiveness of using the SIMKAH application in the marriage registration process, as well as the challenges faced in its implementation. The method used in this research was interviews with key informants, including the head of the KUA and the prospective bride and groom. Data was collected through direct observation and analysis of documents related to marriage registration procedures. This research also involves qualitative analysis to understand the experiences and challenges faced by catins in using SIMKAH. The research results show that the implementation of SIMKAH has the potential to improve the quality of marriage services, but there are still several problems that need to be overcome, such as obstacles in using the application and administrative requirements as well as server slots which are very lacking and not yet fully understood by KUA officers. Thus, this research does not only focus on the SIMKAH application, but also covers other aspects that influence marriage administration data collection, so that it can provide a more comprehensive picture of the situation in the Central City KUA, Gorontalo City. Through this research, it is hoped that an effective solution can be found to improve the quality of marriage services at KUA, as well as provide recommendations for the development of a better management information system in the future.